(3GdahGcg GdOhGfi Ydi QSGdI Hf CHj RjO GdbjQhGfis - (3CMeO Zfjee GdfaQGhis; (3CHh eMeO YHO Gddg Hf CHj RjO GdeGdcj GdbjQhGfj,J (B389 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3jHOC HHGH ai CMcGe GdLgGO gh dZI GdJYH hGdeTbI s
(3BNQgG (B:s
(3fGbU , hGdehLhO ajgG bhdg (B: (3hCaVd ef PcQ Gddg HGddSGf PcQ Gdgd YfO GeQg hfgjg ajJeKd eG CeQg Gddg Hg hjfJgi YeG fgi Gddg Yfg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eaccg s
(3hNWgG Objb s
(3eYfhfI HGdMHQ GdCMeQ s
(3hYdjgG JYdjbGJ heWGdYI s
Keywords: (3Gdabg GdeGdcjs